RESOURCE- AND POWER SAVING TECHNOLOGY OF ELECTROMAGNETIC WELDING - A. V. Miranovich; Zh. A. Mrochek; L. M. Kozhuro (Наука и техника)
The paper contains results of investigation concerning various designs of magnetic systems applied in devices for electromagnetic welding (EMW) of ferropowder on flat surfaces of parts. It is shown that the most effective magnetic system is based on the constant magnets which provides stable and steady process of depositing coatings and increases productivity of EMW process.